WABAH COVID 19 DAN JAMINAN PERLINDUNGAN ALLAH DALAM MAZMUR 23 - Samarenna, Desti (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
This article focuses on the COVID-19 information that has hit various countries in the world and results in high mortality rates. In Indonesia, various information emerged from social media that caused pressure, fear and even stress. This article is a literature review with a qualitative approach to the text of Psalm 23 about attitudes taken to deal with pressure or COVID-19. The purpose of writing is to raise the theological significance of Psalm 23 and implement it into the life experiences of believers today, where everyone is in a plague situation. Psalm 23 is considered appropriate because it talks about three themes namely the exposition in this paper namely nurture (vv. 1-3), guarding (v. 4) and fellowship with God (vv. 5-6). The analysis is carried out by conducting a hermenetic study, which is combined with narrative analysis.